2023
DOI: 10.1227/neu.0000000000002326
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Vagus Nerve Stimulation: Case Series Outcomes and Future Directions

Abstract: BACKGROUND:Vagus nerve stimulation (VNS) is a neuromodulatory procedure most extensively studied as an adjunct to medically refractory epilepsy. Despite widespread adoption and decades of clinical experience, clinical predictors of response to VNS remain unclear.OBJECTIVE:To evaluate a retrospective cohort of pediatric patients undergoing VNS at our institution to better understand who may benefit from VNS and identify factors which may predict response to VNS.METHODS:We conducted a retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This study did not find a clear correlation between the duration of epilepsy and the efficacy of VNS ( P = 0.917). LoPresti et al found that brain atrophy was associated with worse VNS outcomes, while dysplastic hippocampus and chronic periventricular leukomalacia findings were found to be associated with better VNS outcomes ( 18 ). It has also been shown that patients with low seizure frequency (< 20 seizures/month) have a better prognosis ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study did not find a clear correlation between the duration of epilepsy and the efficacy of VNS ( P = 0.917). LoPresti et al found that brain atrophy was associated with worse VNS outcomes, while dysplastic hippocampus and chronic periventricular leukomalacia findings were found to be associated with better VNS outcomes ( 18 ). It has also been shown that patients with low seizure frequency (< 20 seizures/month) have a better prognosis ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, VNS is still a treatment that relies on the clinician's experience, and the clinical outcome of patients cannot be predicted preoperatively. Although many studies have explored the predictive factors of VNS efficacy in recent years, the results are not entirely consistent (18,19,28). Currently, there is still a lack of preoperative predictive indexes for the efficacy of VNS in the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation